The status quo’s role in improving the estimation of willingness to pay in choice experiments - MAXIM, Alexandru; ROMAN, Teodora (European Journal of Sustainable Development, 2019)
European household consumers have seen a gradual increase in the cost of their electricity bill, partly due to ambitious support policies for the development of renewable energy. Some consumers may have a higher willingness to pay (WTP) for clean energy, which could constitute a competitive advantage for electricity suppliers branding themselves as “sustainable”. A discrete choice experiment has been used in order to estimate the WTP of households for renewable energy. For the last decade, researchers have debated whether to add a “status quo” / “not willing to pay for changes” option in the experimental design, as this may generate complications and not add sufficient benefits. In this paper we use an original approach based on two parallel model estimations applied to the same sample of respondents in order to demonstrate the effect of adding a “status quo” option. Our results show that not including it would have led to an overestimation of about one third of the respondents? WTP. While more research on the topic is needed, we demonstrate the risk of simplifying the experimental design and propose a facile method of enhancing the experiment with a dual model design. Keywords: discrete choice experiment, status quo, renewable energy, household consumers, willingness to pay